2019
DOI: 10.1038/s41597-019-0210-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of cotton Gossypium hirsutum challenged with low-temperature gradients stress

Abstract: Gossypium hirsutum, a cotton species widely cultivated around the world, is a typical cold-sensitive crop. Low-temperature (LT) stress is one of the main environmental stressors that can affect growth and the quality of cotton fibers. LT is also a major challenge for cotton survival, growth maturity and geographical distribution. However, few genome-wide transcriptional response and profiling datasets are available to explore the LT-tolerant mechanism of cotton. This study treated G. hirsutum with four LT grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The results showed that GhRPS6 (Gh_D13G0519.1) of G. hirsutum was in the same branch as GOBAR DD31969 of G. barbadense, and the protein sequence was closest to that of A. thaliana AT4G31700 ( Figure 1a). Upland cotton (G. hirsutum) is the most widely cultivated species globally [31]. To better understand the evolutionary relationship between different members of the GhRPS6 gene family, we constructed separate rootless phylogenetic trees using GhRPS6 DNA sequences and performed comparative analysis of intron-exon structures (Figure 1b,d).…”
Section: Ghrps6 Gene Cloning and Bioinformatics Analysismentioning
confidence: 99%
“…The results showed that GhRPS6 (Gh_D13G0519.1) of G. hirsutum was in the same branch as GOBAR DD31969 of G. barbadense, and the protein sequence was closest to that of A. thaliana AT4G31700 ( Figure 1a). Upland cotton (G. hirsutum) is the most widely cultivated species globally [31]. To better understand the evolutionary relationship between different members of the GhRPS6 gene family, we constructed separate rootless phylogenetic trees using GhRPS6 DNA sequences and performed comparative analysis of intron-exon structures (Figure 1b,d).…”
Section: Ghrps6 Gene Cloning and Bioinformatics Analysismentioning
confidence: 99%
“…Many characters have been targeted to find the key responsible genes and pathways, especially fiber initiation, and elongation being highly focused up on [61][62][63][64][65][66][67][68]. Other characters like Green and Brown colored cotton [69-71], Cadmium tolerance [72], Cold stress [73], Drought stress [74], Nematode resistance [75], Semigamy in Pima cotton [76], Whitefly mediated cotton leaf curl infection transcriptome [77], the transcriptome of Mepiquat chloride-induced compact types using in cotton [78] have also been done in cotton. Many studies have been carried out to identify genes that are differentially expressed, however paucity of the causes of the differential expression, hints us towards epigenetic regulations and transcription factors as the probable cause.…”
Section: Transcriptome Studies In Cottonmentioning
confidence: 99%
“…In rice, transcriptomic analysis has been used to study the cold response mechanisms of leaves, roots, and shoots at the seedling stage, as well as anthers at the reproductive stage [30][31][32]. Recently, scientists have studied the cold response mechanisms of true cotton leaves at the seedling stage and seed embryos at the germination stage by using RNA-seq technology [3,33]. However, reports on the transcriptome profiling of cotton seedling cotyledons under cold stress had not been disclosed.…”
Section: Introductionmentioning
confidence: 99%
“…They are not only the essential autotrophic organs before the first true leaf appeared but also the most vulnerable parts to cold stress. Previous studies on the response of cotton to cold stress mainly focused on the germination stage of seeds and the true leaf stage of seedlings [3,33]. However, the seedling cotyledons are more susceptible to cold stress than true leaves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation